2012
DOI: 10.1186/1756-0500-5-524
|View full text |Cite
|
Sign up to set email alerts
|

Why is the Liverpool care pathway used for some dying cancer patients and not others? Healthcare professionals’ perspectives

Abstract: BackgroundDespite evidence suggesting that the Liverpool Care Pathway for the Dying Patient is a structured and proficient means of supporting care delivery in the last hours or days of life, discrepancies in uptake are widespread. This exploratory study sought to understand why patients dying of cancer in oncology wards of one hospital trust were, or were not, supported by the LCP. A purposive qualitative case study design was used; each case represented a patient who had died and their most involved nurse an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In a mixed‐methods study, RNs, ENs, social workers, a medical intern, a medical fellow and a medical consultant were supported when using the LCP in acute care settings in areas such as diagnosing dying, symptom control, consulting a specialist in palliative care, knowledge, confidence, communication and teamwork . Qualitative studies also support the value of using the LCP in oncology hospital wards , acute hospitals and hospices . However, in the UK there has been debate and criticism over the use of the LCP.…”
Section: Introductionmentioning
confidence: 99%
“…In a mixed‐methods study, RNs, ENs, social workers, a medical intern, a medical fellow and a medical consultant were supported when using the LCP in acute care settings in areas such as diagnosing dying, symptom control, consulting a specialist in palliative care, knowledge, confidence, communication and teamwork . Qualitative studies also support the value of using the LCP in oncology hospital wards , acute hospitals and hospices . However, in the UK there has been debate and criticism over the use of the LCP.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Previous studies have shown that end-of-life ICPs, particularly the LCP, are generally well regarded by health care professionals and are perceived to improve the care of dying patients, particularly with regard to symptom control, communication and documentation of care. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The LCP is now used in over 20 countries worldwide. [27] Nevertheless, the evidence supporting the LCP's effectiveness in obtaining a good death remains equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Our data show a benefit and necessity for routine IPT reassessment during care for the dying. This assessment is an important contributing factor in diagnosing non-dying patients in the LCP [ 53 ]. Interprofessional teamwork has received increasing attention within healthcare and care for the dying in particular [ 17 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This assessment is an important contributing factor in diagnosing non-dying patients in the LCP [ 53 ]. Interprofessional teamwork has received increasing attention within healthcare and care for the dying in particular [ 17 , 53 ]. However, it takes time to control symptoms, ensure good communication and support families within a team approach [ 9 ].…”
Section: Discussionmentioning
confidence: 99%